INTERFERENSI BAHASA BATAK MANDAILING PADA PENGGUNAAN BAHASA INDONESIA DALAM INTERAKSI KELAS DI KELAS VII MADRASYAH TSANAWIYAH SWASTA - Siti Jahria Sitompul (Universitas Negeri Medan, 2015)
The objective of the research is to find out the interference of bataklanguage into indonesian language in interaction class. The data is found frominteraction class 2013’. This research used theory of bilingual, languageinterference choice in order to analyse the data. The result of this research has found11 forms of batak’s language interference to the indonesian language includingmorfologi and prefosisi.